ANALISIS KUALITAS KREDIT PT BANK PEMBANGUNAN DAERAH JAWA TIMUR Tbk BERDASARKAN RASIO NON-PERFORMING LOAN (NPL) DAN LOAN TO DEPOSIT RATIO (LDR) PERIODE 2020–2024 - Bayu Rifqie Syahbawono; Syarifah Ratih Kartika Sari; Fatchur Rochman (Universitas Merdeka Madiun, 2026)
This study aims to analyze the credit quality of PT Bank Pembangunan Daerah Jawa Timur Tbk during the 2020–2024 period using the Non-Performing Loan (NPL) and Loan to Deposit Ratio (LDR) ratios. This research employed a quantitative descriptive method using secondary data obtained from the company’s annual reports. The analysis was conducted using a time series approach and compared with bank soundness standards issued by the Financial Services Authority (OJK). The results show that the NPL ratio fluctuated during the observation period but remained within the healthy category. Meanwhile, the LDR ratio consistently indicated very strong liquidity, although the bank’s intermediation function had not been fully optimized. Overall, the study concludes that PT Bank Pembangunan Daerah Jawa Timur Tbk maintained healthy credit quality and strong liquidity during the 2020–2024 period.